Novel submucosal injection material comprising fully synthetic and self-assembling peptide solution in endoscopic submucosal dissection: A pilot study - Kengo Kasuga; Keigo Sato; Ko Nakata; Hirohito Tanaka; Hiroko Hosaka; Shiko Kuribayashi; Yoji Takeuchi; Toshio Uraoka (Endoscopy International Open)
Endoscopic submucosal dissection (ESD) requires an injection solution to create a submucosal cushion for safe endoscopic resection. This study evaluated the safety and feasibility of a new injection solution (PuraLift) in ESD for early-stage gastrointestinal tumors. This prospective, single-arm, single-center pilot study included 11 patients with gastrointestinal neoplasms of the stomach (n = 5) or colorectum (n = 6) who underwent ESD. All patients underwent outpatient follow-up at week 4 to confirm presence or absence of adverse events (AEs). All underwent protocol treatment and post-treatment follow-up. None of the AEs were judged to have a cause-and-effect relationship with the study. Questionnaires to the operators who performed the protocol treatment and assistants who performed submucosal injections were evaluated in comparison with saline, and maintenance of mucosal lifting was long, comparable, and short (9/2/0). En bloc and R0 resections were achieved in all patients without intraprocedural AEs. Median size of the specimens was 40 mm (range, 20–70). Median excision time was 52 minutes (range, 22–130). Median volume of PuraLift was 32 mL (range, 22–130). No postoperative bleeding or delayed perforation was observed in any patient. The novel injectable material, PuraLift, can potentially ensure safe and feasible ESD.